The Effect of Fibrinogen Genotype on Fibrinogen Levels after Strenuous Physical Exercise - Brull, D.J.; Dhamrait, S.; Moulding, R.; Rumley, A.; Lowe, G. D. O.; World, M. J.; Humphries, S. E.; Montgomery, H. E. (Thrombosis and Haemostasis, 2002)
We have examined the effect of two f3-fibrinogen gene promoter polymorphisms (-455G>A and -854G>A) on the fibrinogen response to severe exercise in a group of male army recruits undergoing basic training. Fibrinogen was measured pre-training and again serially after severe 48 h final military exercise (FME). Out of 884 subjects, 762 completed training of whom 250 were selected for post-FME study. Fibrinogen levels (g/l) were significantly elevated over baseline levels 2, 48 and 96 h after FME, representing increases of 15.7%, 3.4% and 7.6% (p <0.005; p = 0.05 and p <0.005 respectively), with higher levels in -455A allele carriers than genotype -455GG: 3.17 ± 0.05 vs. 2.94 ± 0.05 (p <0.001), 2.86 ± 0.05 vs. 2.60 ± 0.05 (p <0.0005) and 2.98 ± 0.06 vs. 2.69 ± 0.06 (p <0.0005) at 2, 48 and 96 h respectively. There was no effect of the -854G>A polymorphism on fibrinogen, even after taking into account f3-fibrinogen -455 genotype. Thus the fibrinogen -455G>A polymorphism influences fibrinogen levels following exercise. The effect of genotype might be clinically relevant at times of hyperfibrinogenaemia such as following an acute inflammatory response.
Keywords: Fibrinogen; genetics; exercise